Joyce and Weil's Information Processing Model in Improving the Quality of English Language Learning at Madrasah Aliyah Palopo - Munir, Bayanuddin (Riwayat: Educational Journal of History and Humanities, 2024)
This research illustrates application of information processing models in improving the quality of English language learning.This research was carried out as Classroom Action Research (PTK). StudyThis was carried out at MAN Palopo with the research subjects being class XI students with a total of 22 students, 1 teacher and the principal. Sources of data obtained from these students include student formative tests in working on questions given at the end of the cycle. Results of observation sheets to measure improvements in student learning outcomes with the application of the modelInformation processing. Observation results and field notes related to student activities in ongoing English language learning.The results of research and analysis conclude that improving the quality of learning in research.The application of the information processing model is suitable for raising student values and students' interest in learning with the information processing concept having the mission of helping students to concentrate on a domain that they can master. Supervision/control, helps students develop a conceptual understanding of a particular domain. 2. Increased student learning outcomes from each cycle, namely in the competency test the average score was 69 in cycle I was an average score of 68.4 and in cycle IV the average score was 76.77.